Exploring the Benefits of Remanufacture during Product Prototyping: A Cost and Time Based Analysis. (May 2022) - Real, R. M.; Snider, C.; Hicks, B.
Abstract: Whilst remanufacture is identified as a key enabler for sustainable manufacture in future industry, its role within the context of new product development remains unclear. Where prototypes often go through multiple iterations with varying degrees of change, could remanufacture be adopted to reduce the time and cost components of design iteration? This paper presents a computational study to explore the potential savings afforded by remanufacture across stages of a rapid prototyping process. Results suggest significant reductions to development time and cost can be achieved.